2011
DOI: 10.3390/s111110586
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Radiometric Calibration of ALS Intensity Data: Effects on Accuracy and Target Classification

Abstract: Radiometric calibration of airborne laser scanning (ALS) intensity data aims at retrieving a value related to the target scattering properties, which is independent on the instrument or flight parameters. The aim of a calibration procedure is also to be able to compare results from different flights and instruments, but practical applications are sparsely available, and the performance of calibration methods for this purpose needs to be further assessed. We have studied the radiometric calibration with data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…Further processing was carried out at the FGI. A range correction was applied to the intensity information to make relative radiometric calibration (Ahokas et al, 2006;Kaasalainen et al, 2011). As expected, our preliminary analyses with uncorrected data showed that intensity values were highest in the middle of a flight line and decreased as the distance from the scanner increased.…”
Section: Multispectral Als Datamentioning
confidence: 56%
“…Further processing was carried out at the FGI. A range correction was applied to the intensity information to make relative radiometric calibration (Ahokas et al, 2006;Kaasalainen et al, 2011). As expected, our preliminary analyses with uncorrected data showed that intensity values were highest in the middle of a flight line and decreased as the distance from the scanner increased.…”
Section: Multispectral Als Datamentioning
confidence: 56%
“…Ya que la zona de estudio es extensa y el terreno muestra una alta variabilidad en cuanto a pendientes y altitudes, los valores de intensidad se normalizaron en función de un rango estándar, con el fin de eliminar la dependencia de los valores de intensidad con respecto a la altura de vuelo (García et al 2010) y al ángulo de incidencia (Kaasalainen et al 2011). Así, la intensidad normalizada (I') se obtuvo mediante la multiplicación del valor bruto de la intensidad (I) por el cociente entre el rango de cada retorno (rg, m) y el rango estándar (rg s , m) (en este caso 1.000 m) y por el inverso del coseno del ángulo de incidencia del rayo láser (α, radianes).…”
Section: Normalización De La Intensidad De Los Datos Lidarunclassified
“…Although Equation (4) is a simplified mathematical law and the light scattering behaviors of most natural surfaces are not Lambertian, many studies have reported that incidence angle dependence for many surfaces approximately follows the cosθ relation [4,7,8,[15][16][17][18]. However, the accuracy of the correction of the incidence angle effect can be further improved.…”
Section: Existing Correction Methods For Distance and Incidence Anglementioning
confidence: 99%
“…For relative correction [17], only a value related to the reflectance should be acquired so that f 1 pρ s q can be arbitrarily defined; this scenario means that the corrected intensity value calculated by Equation (23) is relative but comparable. Selecting different reference targets leads to different relative correction results.…”
Section: Proposed Model For Intensity Correctionmentioning
confidence: 99%
See 1 more Smart Citation